SUPLEMENTASI YODIDA PADA TELUR AYAM TERHADAP ASUPAN PROTEIN DAN ZAT GIZI IODUM SERTA KONSENTRASI BELAJAR SISWA SEKOLAH DASAR DON BOSCO KOTA BITUNG - Daniel Robert; I Made Djendra (Jurnal GIZIDO, 2014)
Background. Unbalancedfood consumptionandlongmaycausenutritional problems. Goodnutritionallowsphysicalgrowth, brain development, employability andgeneral health. Children whoaremalnourishedwill be impairedphysicalgrowth, mentaland intellectual.Purpose. Knowingthe influence ofiodidesupplementation, proteinandnutrientintakeof iodineto theconcentration ofelementaryschoolstudents' learning.Method. The research is aquasi-experimentalpretest-posttest with. The sampleconsists ofthetreatment groupandthe controlgroupby the number of98samples, determinedpurposive. DataanalysisusingSPSS18.0andtestdata usingindipendenttestandPairedSamples TestSamples Test.Results. Protein intakein the treatment groupbeforesupplementationwith an averageof49.16gand50.93gthereafter, andprotein intakein the control group48.36g, thenaftergiving48.37g. Concentrationstudentsbefore08.00hoursin the morningsupplementationin thetreatment group52.12pointsand45.81pointsin the control group, thenthe concentrationofstudentsat10.00am50.16pointsin the treatment group, thecontrol group43.57points.Iodineintakebeforegivingsupplementationin the treatment groupis47.09g, andaftergiving78.73g,iodineintakein the control groupbeforesupplementation46.87g, 74.34gandafter being given.Conclusion. There is noeffect ofsupplementationon theintakeof iodizedeggprotein(P =0.771), noeffect ofsupplementationoneggiodizediodineintake(p =0.000), andthere isthe effectofsupplementationof iodizedeggsatthe concentrations studied(p =0.029).